Respostas
respondido por:
2
Boa tarde Raineruriel
a) (x - 8)² + (y - 4)² = 25
x² - 16x + 64 + y² - 8y + 16 - 25 = 0
x² + y² - 16x - 8y + 55 = 0
b) (x + 3)² + (y - 1)² = 4
x² + 6x + 9 + y² - 2y + 1 - 4 = 0
x² + y² + 6x - 2y + 6 = 0
a) (x - 8)² + (y - 4)² = 25
x² - 16x + 64 + y² - 8y + 16 - 25 = 0
x² + y² - 16x - 8y + 55 = 0
b) (x + 3)² + (y - 1)² = 4
x² + 6x + 9 + y² - 2y + 1 - 4 = 0
x² + y² + 6x - 2y + 6 = 0
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás